Optimasi Work Instruction Setting Die Mesin AIDA 200 Ton Menggunakan Metode SMED - Ramadhani, Velia Sagita; Nisah, Firda Ainun (Universitas Indraprasta PGRI Jakarta, 2025)
PT XYZ is a company engaged in manufacturing automotive components. The company produces and distributes car body parts by performing stamping, welding, assembling, and tooling processes. In the production process, there is a die setting activity as one of the processes that must be passed to produce a part. From the results of observations made on the 200 TON AIDA Press machine die setting activity in accordance with the existing Work Instruction, the average time obtained in the die setting activity is 21 minutes/order. This is one of the shortcomings that creates a 10-minute gap from the target set by the company. So that increasing productivity between workers and machines is needed to achieve these targets. The purpose of this research is to find out, analyze, process, and provide suggestions for improvements to the problem of the long die setting time of the 200 TON AIDA Press machine. The method used to make improvements is Single Minute Exchange of Dies (SMED). SMED succeeded in reducing die setting time quite significantly with an initial die setting duration of 21.56 minutes to 10.46 minutes, normal time from 24 minutes to 12 minutes, standard time from 32 minutes to 16 minutes, and the percentage reduction obtained was 51.48%.